RETENTION OF SCHOOL VIOLENCE UNDER THE PERSPECTIVE OF A PUBLIC SCHOOL EMPLOYEES - Netto, Luciana (2013)
http://dx.doi.org/10.5902/217976928100Aim: to identify strategies to curb school violence in vision by employees in a public school in the city of Divinópolis-MG. Methods: this is a descriptive and qualitative study. Data were collected through interviews and later transcribed, evaluated by means of content analysis. Results: from repeated speeches were organized two categories: The role of schools and the role of the family. Corroborated the of multiple problems situation, the respondents not told with measures that articulate the training required for teachers. Conclusion: it appears that the respondents have knowledge of a larger number of situations of conflict between teacher and student, which makes these statements consistent with the actual need of that environment. We also emphasize the urgent need to integrate actions with strategies to involve employees in the education and training required for teachers.